Homestead pond aquaculture innovation for food production in the context of climate change in the Mekong Delta, Cambodia - Tuy, Sinak; Freed, Sarah; Sithirith, Mak; Sean, Vichet; Kong, Heng; Kongkroy, Chay; Ouk, Hak; Kong, Sovannara (WorldFish, 2024)
The Asia Mega Deltas Initiative (AMD) addresses climate impacts in Asia's deltas, including the Mekong Delta, aiming to adapt deltaic production systems for resilience and reduced environmental footprints. Work Package 1 (WP1) fosters innovation scaling, enhancing sustainable intensification and value chain development through learning alliances involving farmers, local governments, and stakeholders in Cambodia.